ORGANIZATION OF GROUP ACTIVITIES OF OLDER PRESCHOOL CHILDREN IN THE PROCESS OF EXPERIMENTING - Karuk, Inna; Kolesnik, Kateryna; Kryvosheya, Tetiana; Prysiazhniuk, Larysa; Shykyrynska, Oleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The authors of the article analyze the advantages and disadvantages of group activities of older preschool children. The article focuses on the importance of children's experimentation for the versatile development and readiness of older preschool children to study at school. A comparative characteristic of the organization of individual children's experimentation and a group of older preschool children is presented. Based on a survey of older preschool children and their teachers, as well as monitoring the activities of children during experimentation, problematic aspects of organizing group activities of children are identified. Psychological and pedagogical conditions for organizing group activities of older preschool children for effective interaction during experimentation are presented. The expediency of using experimentation as a means of developing children's research activity is substantiated. The specifics of experimentation are indicated. The purpose and structure of experimentation as a kind of games for children's cognitive development are determined. The article also contains a list of devices and materials for arranging the experimentation centre which should be located in a preschool institution according to the thematic principle and teacher’s work plan; due to such centre children will be able to further freely experiment and consolidate the learned material through independent search activities. It is proved that the use of psychological and pedagogical conditions for the organization of group activities of older preschool children in the process of experimentation will contribute to the formation of their beliefs about nature and the world.